Effects of Si and Mg elements on the microstructure of aluminum–steel joints produced by pulsed DE-GMA welding–brazing. (1st September 2013) - Shi, Y; Shao, L; Huang, J; Gu, Y
Abstract : Pulsed double electrode-gas metal arc welding–brazing of aluminum alloy and galvanised steel had been conducted using Al–Si and Al–Mg filler wires, respectively. Good formation and little deformation for the lap joint design were obtained. The microstructure, composition and phase analysis of weld joints were examined using optical microscopy, scanning electron microscopy, energy dispersive spectroscopy, electron probe microanalyser and X-ray diffraction. By comparing the microstructures of weld joints using different welding wires, it was found that intermetallic compound layers formed at the interface of aluminum and galvanised steel weld seam using Al–Si filler wire were composed of a needle-like shape FeAl3 layer at the weld seam side and a flat Fe2 Al5 layer at the galvanised steel side, while a Fe2 Al5 intermetallic compound layer was present when using Al–Mg filler wire and it was tongue-like oriented toward the galvanised steel side, and a FeAl3 zigzag-like intermetallic compound layer was also found at the aluminum side. After the weld samples were peeled down using Al–Si filler wire, the Fe0·7 Al3 Si0·3 phase was detected on the peeled surface of the weld joint. By comparing the intermetallic compounds formed in the weld seam using different welding wires, it indicated that Si had the effects to inhibit the formation of the Fe2 Al5 intermetallic compound by reducing the diffusion rate of Fe by exhibiting the Al–Fe–Si intermetallic compound. Under the constant total current and the same bypass current, the strength of weld joints using Al–Si filler wire is larger than the strength of weld joints using Al–Mg filler wire by tension tests.